2008
DOI: 10.1007/s10562-008-9539-9
|View full text |Cite
|
Sign up to set email alerts
|

Redox Isotherms for Vanadia Supported on Zirconia

Abstract: Redox isotherms were measured for zirconiasupported vanadia between 10 -2 and 10 -28 atm at 748 K for two vanadia loadings, 2.9 and 5.8 V/nm 2 , corresponding to isolated VO 4 species and monolayer, polymeric vanadates. The catalyst with isolated VO 4 species, which is expected to have predominantly V-O-Zr linkages, had a redox isotherm that showed a well-defined step corresponding to one oxygen per V. By contrast, the redox isotherm for the catalyst with polymeric vanadates changed more gradually with P O 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…This 61% transformation of V 5+ → V 4+ after cyclohexane reduction is similar to that of our previous study of 2 ML VO x /α-TiO 2 (110), for which H 2 was used as the reductant and where we saw 100% transformation . It is not surprising to observe this partial reduction of V 5+ to V 4+ in an ambient condition because of the coexistence of multiple chemical states of V. This has similarly been reported for V on silica, alumina, and zirconia, , which, like titania, are also difficult to reduce.…”
supporting
confidence: 89%
“…This 61% transformation of V 5+ → V 4+ after cyclohexane reduction is similar to that of our previous study of 2 ML VO x /α-TiO 2 (110), for which H 2 was used as the reductant and where we saw 100% transformation . It is not surprising to observe this partial reduction of V 5+ to V 4+ in an ambient condition because of the coexistence of multiple chemical states of V. This has similarly been reported for V on silica, alumina, and zirconia, , which, like titania, are also difficult to reduce.…”
supporting
confidence: 89%
“…Shah et al studied redox isotherms of vanadia supported on zirconia for vanadia loadings of 2.5 and 5 wt %, correponding to 2.9, and 5.8 V/nm 2 , respectively. Since the fully vanadia loaded surfaces host about 8 V/nm 2 (Table ), these samples correspond to Θ = 0.36 and 0.72, respectively, and fall in between our Θ = 0.25, 0.5, and 1.0 models.…”
Section: Resultsmentioning
confidence: 99%
“…Since the fully vanadia loaded surfaces host about 8 V/nm 2 (Table ), these samples correspond to Θ = 0.36 and 0.72, respectively, and fall in between our Θ = 0.25, 0.5, and 1.0 models. The numbers given in ref are free energies and refer to one O 2 molecule. With additional data for the corresponding enthalpies from ref and assuming that the entropy change is the same for the different materials (−212 J/molK), we arrive at the following enthalpies of reduction per 1/2 O 2 molecule (eq ) from refs and −225 kJ/mol (2.5%VZr), −129 kJ/mol (5%VZr), −113 kJ/mol (ZrV 2 O 7 ), −143 kJ/mol (V 2 O 5 ), which can be compared with the calculated DFT(PW91) data in Table , that is, about −390 to −410 kJ/mol for small (isolated and dimeric) species, about −150 to −190 kJ/mol for polymeric species, and −186 kJ/mol for V 2 O 5 (ref ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4 †), the rst neighbor structure around V in the OX sample is best reproduced by 2.2 V-O bonds of 1.62 Å and 1.7 V-O bonds of 1.82 Å (Table 1), suggesting a total coordination number N ¼ 4. The small Debye-Waller factor, s 2 (<10 À3 Å2 compared to 5.7 Â 10 À3 from V 2 O 5 analysis), may be indicative of somewhat underestimated value of N, given the strong correlation between s 2 and N. However, the large H/S ratio of $0.55 for the OX VO X indicates a dominant low symmetry coordination conguration around V. Previous studies 14,[37][38][39][40] have suggested that oxide-supported VO X in a V 5+ oxidation state has a VO 4 tetrahedral structure with one V]O bond, one V-O-M support bond (M represents the support metal cation) and two V-O-V bonds. Although EXAFS studies 30,[41][42][43][44] of vanadium oxides on different supports suggested that the VO 4 unit has one V]O bond $1.6 Å and multiple V-O bonds $1.8 Å, our study shows that the OX contains VO 4 tetrahedral units with two short V-O bonds.…”
Section: Resultsmentioning
confidence: 87%